2005
DOI: 10.1348/135910705x26083
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, positive affectivity, and salivary cortisol

Abstract: These findings suggest that positive psychological resources including optimism and generalized positive affect had higher impact on cortisol secretion than their negative counterparts, and point to the need for increased attention to the potential contribution of positive mental states to well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 60 publications
6
72
1
1
Order By: Relevance
“…Because optimistic individuals have positive expectations for the future, they experience less anxiety and daily problems (LaMontagne, Hepworth, Salisbury, & Riley, 2003;Trunzo & Pinto, 2003), they experience more positive emotions (Lai et al, 2005) and they have more life satisfaction (Bailey, Eng, Frisch, & Snyder, 2007;Leung, Moneta, & McBride-Chang, 2005). Thus, they suffer less depressive symptoms because they can deal with problems more strongly (Chang, 1998;Puskar et al, 1999).…”
Section: Optimismmentioning
confidence: 99%
“…Because optimistic individuals have positive expectations for the future, they experience less anxiety and daily problems (LaMontagne, Hepworth, Salisbury, & Riley, 2003;Trunzo & Pinto, 2003), they experience more positive emotions (Lai et al, 2005) and they have more life satisfaction (Bailey, Eng, Frisch, & Snyder, 2007;Leung, Moneta, & McBride-Chang, 2005). Thus, they suffer less depressive symptoms because they can deal with problems more strongly (Chang, 1998;Puskar et al, 1999).…”
Section: Optimismmentioning
confidence: 99%
“…This assertion is supported by a growing body of evidence demonstrating the attenuating effects of positive psychosocial attributes on various components of the diurnal cortisol cycles (e.g., optimism, [27]; positive well-being, [32]; positive affect [33]). The significant effect of Network Cultivation on diurnal cortisol profiles reiterates the importance of proactivity in the social lives of older people, which has been demonstrated in Japanese seniors [34].…”
Section: Social Network Cultivation and Diurnal Cortisol Profiles In mentioning
confidence: 92%
“…Participants were screened to ensure that they were not habitual smokers, had no prior or current diagnoses of psychiatric disorders, cancers, cardiovascular disorders, and were not currently on medications such as estrogen, synthetic glucocorticoids, antisteroid drugs, and antiseizure drugs that would potentially affect cortisol concentrations. The procedure was identical to that adopted in prior studies with Hong Kong Chinese [8,27] and was approved by the relevant approving body of the City University of Hong Kong. In particular, the researcher briefed participants in the first home visit, and provided them with a study pack containing instructions for saliva collection using saliva sampling tubes (Salivettes Sarstedt AG & Co., Nümbrecht, Germany), questionnaires, and a comprehensive description of the procedure of the study.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Various indices of the diurnal cycle of salivary cortisol have been reported to be associated with optimism [40,41], positive affect [42], humor [43], social network characteristics [44], and positive wellbeing [45]. A recent study has also demonstrated a positive association between optimism, a key component of psychological resilience [45], and rate of wound healing in healthy men [19], thus providing support for the role cortisol possibly plays in mediating the relationship between psychological resilience and wound healing.…”
Section: Vulnerability Versus Resilience In Conjugal Bereavementmentioning
confidence: 96%